Au@gap@AuAg Nanorod Side‐by‐Side Assemblies for Ultrasensitive SERS Detection of Mercury and its Transformation. Issue 27 (20th May 2019) - Yuan, Aimeng; Wu, Xiaoling; Li, Xiu; Hao, Changlong; Xu, Chuanlai; Kuang, Hua
Abstract: As one of the most toxic heavy metal elements, mercury ion (Hg 2+ ) and its methylated product, methylmercury (MeHg) can pose a threat to human health and the environment. Herein, a novel Raman biosensor with cascade sensitivity is developed for Hg 2+ detection through Au@gap@AuAg nanorod side‐by‐side assemblies. Due to the strong electromagnetic coupling from the assemblies and core–shell structure, the Raman sensor possesses high sensitivity with the limit of detection (LOD) of 0.001 ng mL ‐1, which is about one order lower than traditional atomic fluorescence spectrometer (AFS) methods. Moreover, the fabricated biosensor is used to measure residual mercury levels in tissues and eggs of hens fed high‐mercury diets, and the results show total mercury in collected egg yolks is 20 times higher than whites. Furthermore, the form of mercury in the eggs is also analyzed by high‐performance liquid chromatography coupled with AFS, and, unexpectedly, the methylated product MeHg tends to only be found in egg whites. These interesting differences may indicate a new research direction for the toxicity of mercury in living organisms, and the developed ultrasensitive Surface Enhanced Raman Scattering (SERS) method could pave a broad way for the application of biosensors in Hg detection. Abstract : A novel Raman biosensor with cascade sensitivity with a limit of detection (LOD) of 0.001 ng mL ‐1 is developed for Hg 2+ detection through Au@gap@AuAg nanorod side‐by‐side assemblies. The fabricated biosensor is used to measure residual mercury levels in tissues and eggs.